Analyzing the Suitability of English Reading Materials: The Correlation between the Readability Level and Narrative Reading Comprehension - Kuswoyo, Adelia Rizca (Raden Intan State Islamic University of Lampung, Indonesia, 2023)
The observed low reading proficiency among Indonesian students can be attributed to several variables, such as the level of readability or the degree of text difficulty. The comprehension of the suitability of texts for students was of utmost importance for English teachers. The correlational research methodology was employed in this study to ascertain the presence or absence of a statistically significant relationship between student reading comprehension and the outcome variable under investigation. The participants of this study consisted of tenth-grade students from SMA Gajah Mada and SMAN 7 Bandar Lampung, who were selected to participate in the research project conducted throughout the 2020-2021 academic year. To acquire pertinent data regarding the reading comprehension abilities of pupils, an assessment specifically designed to evaluate reading comprehension was administered. A total of 12 narrative reading materials were identified in this study, sourced from three different textbooks: the Pathway to English Textbook published by Erlangga, the Talk Active Textbook authored by Yudhistira, and the Bahasa Inggris Textbook developed by the Ministry of Education and Culture. The researcher evaluated text readability using the Flesch Reading Ease Formula, with the subsequent classification of the readability level based on the Common European Framework of Reference for Languages (CEFR) Level. The results of this study revealed a statistically significant positive correlation (r = 0.9054). A selection of six narrative reading materials, deemed suitable for tenth-grade students, was made accessible.